3D porous collagen scaffolds reinforced by glycation with ribose for tissue engineering application. (21st August 2017) - Gostynska, Natalia; Shankar Krishnakumar, Gopal; Campodoni, Elisabetta; Panseri, Silvia; Montesi, Monica; Sprio, Simone; Kon, Elizaveta; Marcacci, Maurilio; Tampieri, Anna; Sandri, Monica
Abstract: In this study, ribose was proposed as a promising, non-toxic, low-cost crosslinker to enhance the structural integrity and stiffness of type I collagen matrices. The main objective was to determine the optimal conditions of glycation by ribose to fabricate 3D porous collagen scaffolds and to verify their effectiveness for use as scaffolds for cartilage tissue engineering, by physicochemical and biological characterization. Two different crosslinking strategies were investigated including variation in the amount of ribose and the time of reaction: pre-crosslinking (PRE) and post-crosslinking (POST). All ribose-glycated collagen scaffolds demonstrated good swelling properties and interconnected porous microstructure suitable for cell growth and colonization. The POST samples were superior to PRE, in terms of porosity, degree of crosslinking, fluid uptake ability, and resistance to enzymatic digestion. Moreover, the mechanical properties of the scaffolds were significantly improved upon glycation when compared to non-crosslinked collagen, manifesting the best performance for POST matrices crosslinked for 5 d and in the highest amount of sugar. In vitro studies analyzing cell–material interactions revealed scaffold cytocompatibility with higher cell viability and cell proliferation as well as higher glycosaminoglycan secretion for POST scaffolds with respect to PRE. This report demonstrated the feasibility of developing 3D collagen scaffolds by ribose glycation and highlighted the POST-crosslinking strategy as being more favorable than the PRE-crosslinking to achieve scaffolds suitable for cartilage regeneration.